NiTiO3 nanoparticles encapsulated with SiO2 prepared by sol-gel method - Lopes, K. P.; Cavalcante, L. S.; Simões, Alexandre Zirpoli [UNESP]; Goncalves, R. F.; Escote, M. T.; Varela, José Arana [UNESP]; Longo, Elson [UNESP]; Leite, E. R. (Springer, 2008)
NiTiO3 (NTO) nanoparticles encapsulated with SiO2 were prepared by the sol-gel method resulting on core-shell structure. Changes on isoelectric point as a function of silica were evaluated by means of zeta potential. The NTO nanoparticles heat treated at 600 degrees C were characterized by X-ray diffraction, transmission electron microscopy (TEM) and energy dispersive X-ray analysis. TEM observations showed that the mean size of NTO is in the range of 2.5-42.5 nm while the thickness of SiO2 shell attained 1.5-3.5 nm approximately.
Keywords: nanoparticles; coating; sol-gel method; NiTiO3; silica